2018
DOI: 10.1029/2018jd028703
|View full text |Cite
|
Sign up to set email alerts
|

On the Statistical Significance of Climatic Trends Estimated From GPS Tropospheric Time Series

Abstract: For more than two decades, Global Positioning System (GPS) tropospheric delays have successfully been exploited to monitor the tropospheric water vapor in near real time and reprocessing mode. Although reprocessed data are considered reliable for climatic research, it is important to address the often present gaps, inhomogeneities, and to use a proper model to describe the stochastic part of the time series so that trustworthy trends are estimated. Having relatively long time series, daily reprocessed troposph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 41 publications
(68 reference statements)
5
27
0
Order By: Relevance
“…Although the GPS-based wet delay is converted into water vapor using the atmospheric weighted mean temperature that is calculated using reanalysis data, the quality of the IWV products does not change compared to using radiosonde temperature measurements (Ning et al 2016b). We inspected a subset of GPS observations north of 658N (Deng et al 2016;Alshawaf et al 2018), which covers 35 sites ( Fig. S2).…”
Section: Cfsrmentioning
confidence: 99%
“…Although the GPS-based wet delay is converted into water vapor using the atmospheric weighted mean temperature that is calculated using reanalysis data, the quality of the IWV products does not change compared to using radiosonde temperature measurements (Ning et al 2016b). We inspected a subset of GPS observations north of 658N (Deng et al 2016;Alshawaf et al 2018), which covers 35 sites ( Fig. S2).…”
Section: Cfsrmentioning
confidence: 99%
“…CC BY 4.0 License. series over Europe, Alshawaf et al (2018) found that the number of years of daily data required to estimate a IWV trend above 0.3 mm/decade is between 28 and 40 years. As we have only 15 years available for most of the stations, our time series is too short to draw firm conclusions on the presence or magnitude of a trend.…”
Section: Long-term Time Variability Of the Iwv Retrievalsmentioning
confidence: 99%
“…Atmospheric water vapor is an important parameter for the climate research (Alshawaf et al, 2018;Balidakis et al, 2018) and a valuable input for numerical weather model (NWM; Gutman et al, 2004;Oigawa et al, 2018). Retrieving precipitable water vapor (PWV) using Global Navigation Satellite System (GNSS) with 1-to 2-mm accuracy has been demonstrated at ground-based stations (Wang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%